Ta’tsīru ṭarīqah al-ghinā’ ‘alā ḥifẓ al-mufradāt fī ta‘līm al-lughah al-‘Arabiyyah li-ṭālibāt al-faṣl al-ḥādī ‘ashara fī al-madrasah al-‘āliyyah al-Islāmiyyah al-ahliyyah “al-Ḥikam” Jatirejo Dīwek Jombang - Devia Ayu Winarsih; Fathur Rohman (Program Studi Pendidikan Bahasa Arab, 2023)
This research was conducted to determine the effect of the Ghina' method on Mufrodat memorization in learning Arabic in class XI MA Al-hikam Jatirejo students in Jombang district. In this study using quantitative methods. With a population of 44 students from class XI Aliyah and a sample of 24 students. Data collection is done by interview (interview), questionnaire (questionnaire), observation (observation) and a combination of the three. While data analysis is after data from all respondents collected. Classical assumption test (normality test, linearity test, heteroscedasticity test), hypothesis test (t-test), coefficient of determination test (R2). Based on the results of data analysis, it is known that there is a significant influence between the effect of the ghina method on vocabulary memorization. This can be demonstrated by a calculated value of 3.997 and a significance value of 0.001 < 0.05. The contribution of the singing method to vocabulary memorization in learning Arabic reaches 42% of the value of R2 = 0.421 which states that the remaining 58% is caused by other factors that affect vocabulary memorization, such as motivation, subjects, hobbies, and others. From testing the proposed hypothesis, a value of 3,997 can be calculated with a significance value of 0.001 < 0.05. So Ho is rejected and Ha is accepted, meaning that there is a significant influence between the way of singing (X) on the variable memorizing vocabulary (Y).